Hubungan di antara tekanan kerja dengann self-esteem di kalangan anggota tentera di kem penrissen Kuching, Sarawak - Nor Salmi, Mat R usli (Universiti Malaysia Sarawak (UNIMAS), 2008)
The purpose of this study is to identify the relationship between stress at workplace and self-esteen among army in the Kem Penrissen Kuching, Sarawak This study is also to identify the relationship between demografi factor age, rank and education leve and self-esteem[. Beside, this study is also to identify the relationship between workload and role and self-esteem. This qualitative study is using questionnaire which has (3) parts that are demographic factor, Occupational Stress Inventory Revised Edition (QSI-R) and Rosenberg Self-esteem Inventory. This study included 80 armys. Descriptive analysis, Spearmen Rho, One Way ANOVA and Pearson were used to measure the relationship between stress at workplace and self-esteem. The result of the correlation analysis showed that there are no significant relation between stress at the workplace and self-esteem. Only role and self-esteem showed a significant relation with self-esteem. The researcher recommended some suggestions to armys, counselling profesionals and future researchers.